Pertumbuhan Batang Pada Beberapa Varietas Kedelai (Glycine max (L.) Merr) Terhadap Jenis Tanah Aluvial, Regosol Dan Latosol - Kurniawan M.R.D; P. S. Ajiningrum (FMIPA : Universitas PGRI Adi Buana, 2020)
This study aims to determine the growth of 10 superior soybean varieties planted in 3 different types of soil (alluvial, regosol and latosol) and to find out whether the 3 types of soil give an effect to the growth of 10 superior soybean varieties viewed from 4 parameters (hypocotyl length, length epicotiles, stem length and stem dry weight).This study used a Randomized Block Design (RBD) consisting of 10 varieties of soybean plants (anjasmoro, argomulyo, detam 1, detam 3 prida, detam 4 prida, detap 1, devon 1, devon 2, yellow gepak and deja 1) and 3 types of soil (alluvial, regosol, and latosol) was repeated 2 times. Data were analyzed using the two-way ANAVA 5% test and the 5% DMRT test. The results showed a significant difference in soybean growth. The best soybean varieties in hypocotyl length are Devon 2, in epicotile length are Anjasmoro, Devon 1 and Devon 2, the stem length and dry weight of the stem are Detap 1. The DMRT test results state that all three soil types (alluvial, regosol and latosol) have influence on the parameters of hypocotyl length and epicotyl length, whereas the parameters of stem length and plant dry weight have no effect. Keywords: Soybean, Variety, Growing test